Criminal Law Enforcement Against Business Actors Involved in the Distribution of Cosmetic Products Without Distribution Permits: A Research Study within the Jurisdiction of the Bireuen District Court - Rachmi Martiya; Ida Keumala Jeumpa; Sulaiman Sulaiman (International Journal of Law, Crime and Justice, 2026)
Article 435 of Law Number 17 of 2023 concerning Health prohibits any person from producing or distributing pharmaceutical preparations, including cosmetics, that do not meet safety, efficacy, quality, and licensing standards. However, the circulation of cosmetics without distribution permits is still frequently found, including in Bireuen Regency. This condition indicates that law enforcement against illegal cosmetic business actors has not been optimally implemented. This study aims to analyze criminal law enforcement against business actors involved in the distribution of cosmetics without distribution permits within the jurisdiction of the Bireuen District Court, examine the obstacles encountered, and identify the criminological factors underlying the commission of such offenses. The research method employed is empirical juridical research using statutory, case, and criminological approaches through library research and field research conducted by interviews with the Indonesian Food and Drug Authority (BPOM), police, prosecutors, and business actors. The results of the study show that law enforcement against the distribution of cosmetics without distribution permits has not been effective due to weak supervision of digital trade, limited monitoring facilities, low public legal awareness, and relatively light criminal sanctions that fail to create a deterrent effect. From a criminological perspective, these offenses are influenced by economic factors, high public demand for instant cosmetic products, the development of social media and e-commerce, as well as weak supervision and social control. It is recommended that digital trade supervision be strengthened, inter-agency coordination among law enforcement institutions be improved, and stricter sanctions be imposed on offenders, particularly recidivists, in order to enhance public health protection and the effectiveness of law enforcement.